Vegetable Oils in the Production of Biodegradable Alkyd Resins - Bartkowiak, Marcin; Milchert, Eugeniusz; Sałaciński, Łukasz (Mini-Reviews in Organic Chemistry, 2019)
A review of the technological principles of the production of alkyd resins modified with vegetable oils has been presented. Reactions and transformations occurring during the crosslinking in the presence of unsaturated fatty acids and mono-, di- and triglycerides have been described. Influence of the addition of other resins to modified glyptals and pentaphthalates have been presented. Research trends indicate the growing importance of nanomaterials in the preparation of alkyd coatings with improved properties.
Keywords: pentaphthalates